Awareness of Central Luminance Edge is Crucial for the Craik-O’Brien-Cornsweet Effect - Masuda, Ayako; Watanabe, Junji; Terao, Masahiko; Watanabe, Masataka; Yagi, Akihiro; Maruya, Kazushi (Frontiers in Human Neuroscience, 2011)
The Craik-O’Brien-Cornsweet (COC) effect demonstrates that perceived lightness depends not only on the retinal input at corresponding visual areas but also on distal retinal inputs. In the COC effect, the central edge of an opposing pair of luminance gradients (COC edge) makes adjoining regions with identical luminance appear to be different. To investigate the underlying mechanisms of the effect, we examined whether the subjective awareness of the COC edge is necessary for the generation of the effect. We manipulated the visibility of the COC edge using visual backward masking and continuous flash suppression while monitoring subjective reports regarding online percepts and aftereffects of adaptation. Psychophysical results showed that the online percept of the COC effect nearly vanishes in conditions where the COC edge is rendered invisible. On the other hand, the results of adaptation experiments showed that the COC edge is still processed at the early stage even under the perceptual suppression. These results suggest that processing of the COC edge at the early stage is not sufficient for generating the COC effect, and that subjective awareness of the COC edge is necessary.